Dissecting the KNDy hypothesis: KNDy neuron-derived kisspeptins are dispensable for puberty but essential for preserved female fertility and gonadotropin pulsatility - Velasco Immaculada; Franssen Delphine; Daza-Dueñas Silvia; Skrapits Katalin; Takács Szabolcs; Torres Encarnacion; Rodríguez-Vazquez Elvira; Ruiz-Cruz Miguel; León Silvia; Kukoricza Krisztina; Zhang Fu-Ping; Ruohonen Suvi; et al. (Elsevier Inc., 2025)
BACKGROUND
Kiss1 neurons in the hypothalamic arcuate-nucleus (ARC) play key roles in the control of GnRH pulsatility and fertility. A fraction of ARC Kiss1 neurons, termed KNDy, co-express neurokinin B (NKB; encoded by Tac2). Yet, NKB- and Kiss1-only neurons are also found in the ARC, while a second major Kiss1-neuronal population is present in the rostral hypothalamus. The specific contribution of different Kiss1 neuron sub-sets and kisspeptins originating from them to the control of reproduction and eventually other bodily functions remains to be fully determined.
METHODS
To tease apart the physiological roles of KNDy-born kisspeptins, conditional ablation of Kiss1 in Tac2-expressing cells was implemented in vivo. To this end, mice with Tac2 cell-specific Kiss1 KO (TaKKO) were generated and subjected to extensive reproductive and metabolic characterization.
RESULTS
TaKKO mice displayed reduced ARC kisspeptin content and Kiss1 expression, with greater suppression in females, which was detectable at infantile-pubertal age. In contrast, Tac2/NKB levels were fully preserved. Despite the drop of ARC Kiss1/kisspeptin, pubertal timing was normal in TaKKO mice of both sexes. However, young-adult TaKKO females displayed disturbed LH pulsatility and sex steroid levels, with suppressed basal LH and pre-ovulatory LH surges, early-onset subfertility and premature ovarian insufficiency. Conversely, testicular histology and fertility were grossly conserved in TaKKO males. Ablation of Kiss1 in Tac2-cells led also to sex-dependent alterations in body composition, glucose homeostasis, especially in males, and locomotor activity, specifically in females.
CONCLUSIONS
Our data document that KNDy-born kisspeptins are dispensable/compensable for puberty in both sexes, but required for maintenance of female gonadotropin pulsatility and fertility, as well as for adult metabolic homeostasis.
SIGNIFICANCE STATEMENT
Neurons in the hypothalamic arcuate nucleus (ARC) co-expressing kisspeptins and NKB, named KNDy, have been recently suggested to play a key role in pulsatile secretion of gonadotropins, and hence reproduction. However, the relative contribution of this Kiss1 neuronal-subset, vs. ARC Kiss1-only and NKB-only neurons, as well as other Kiss1 neuronal populations, has not been assessed in physiological settings. We report here findings in a novel mouse-model with elimination of KNDy-born kisspeptins, without altering other kisspeptin compartments. Our data highlights the heterogeneity of ARC Kiss1 populations and document that, while dispensable/compensable for puberty, KNDy-born kisspeptins are required for proper gonadotropin pulsatility and fertility, specifically in females, and adult metabolic homeostasis. Characterization of this functional diversity is especially relevant, considering the potential of kisspeptin-based therapies for management of human reproductive disorders.